2016
DOI: 10.1136/bcr-2016-217015
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium apiospermum: a rare cause of malignant otitis externa

Abstract: A 79-year-old man, with a history of well-controlled diabetes mellitus, presented with left-sided otalgia. With an initial diagnosis of simple otitis externa, he was discharged on topical drops. He represented 2 months later with worsening otalgia and discharge. A diagnosis of malignant otitis externa was made based on clinical and radiological findings. Intravenous Tazocin and Gentamicin were given based on previous bacterial culture from ear swabs. The patient failed to improve and developed left-sided facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Recent studies on MOE have reported increased causative pathogen diversity: Klebsiella species (1), Aspergillus avus (3), and Actinomyces (6). Furthermore, Mc Laren et al described MOE with a rare fungal etiologic pathogen -Scedosporium apiospermum (7). In all cases, including ours, DM was associated co-morbidity.…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies on MOE have reported increased causative pathogen diversity: Klebsiella species (1), Aspergillus avus (3), and Actinomyces (6). Furthermore, Mc Laren et al described MOE with a rare fungal etiologic pathogen -Scedosporium apiospermum (7). In all cases, including ours, DM was associated co-morbidity.…”
Section: Discussionmentioning
confidence: 53%
“…The 68 studies included a total of 74 individual cases of fungal TBO (Tables 3 and 4) (8,12,24–89). The mean age (SD) was 55.5 (23.3) years, and 74.3% (55/74) were male.…”
Section: Resultsmentioning
confidence: 99%
“…SBO secondary to fungal species, particularly with S. apiospermum, can lead to fatal complications such as mycotic aneurysms and cerebral infractions [ 3 , 5 ]. In addition, delay in early recognition and treatment can also lead to cranial nerve palsies, intracranial abscesses, and sinus thrombosis [ 6 ]. Johnson et al reported that mortality in SBO is high and can reach up to 10 to 20% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%